Antiproliferative Activity of Crude Marcescin on Human Laryngx Epidermoid Carcinoma (Hep-2) Cell Line in Vitro Study - Abdulredha, Riad M.; Hind Hussein Obaid, (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2025)
Marcescin is a bacteriocin that is extracted from isolates of Serratia marcescens, which is a gram-negative bacterium that belongs to the family Enterobacteraeaceae and is considered a nosocomial pathogenic bacteria. In this research, the toxic effect of crude marcescin extracted from the S. marcescens bacteria on the human laryngx epidermoid carcinoma (Hep-2) cell line was investigated. S. marcescens was isolated from blood, urine, and stool samples of patients from Nursing House Hospital, Baghdad Teaching Hospital, and Teaching Laboratories of Medical City by using a series of dilutions to concentrations of (0.00, 1.95, 3.9, 7.8, 15.62, 31.25, 62.5, 125, 250, 500, and 1000) µg/ml and an exposure time of (24, 48, and 72) hours. The results showed significant differences (P≤0.05) in the IR values (100–2%) at the concentrations (1000–1.95) µg/ml when compared with the control (100%); there were also significant differences after 48 and 72 hours. The results showed that high concentrations caused a high rate of inhibition at concentrations (1000, 500, and 250) µg/m where the rate of inhibition was (100, 67, and 58) after 24 hours, then the rate of inhibition began to decrease gradually, reaching 2% at the lowest concentration of 1.95. It is clear that Hep-2 cells are sensitive to marcescin, and their sensitivity increases exponentially with increasing concentration and time of exposure